The genome sequence of the meadow plant bug, Leptopterna dolabrata (Linnaeus, 1758) [version 1; peer review: 2 approved] - Laurence Livermore; Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from an individual male Leptopterna dolabrata (the meadow plant bug; Arthropoda; Insecta; Hemiptera; Miridae). The genome sequence is 987.9 megabases in span. Most of the assembly is scaffolded into 17 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 18.18 kilobases in length.